Reference Charts for Neonatal Cranial Volume Based on 3D Laser Scanning to Monitor Head Growth - Vermeulen, Marijn Jorien; Burkhardt, Wolfram; Fritze, Anne; Roelants, Jorine; Mense, Lars; Willemsen, Sten; Rüdiger, Mario (Frontiers in Pediatrics, 2021)
Background: Postnatal brain growth is an important predictor of neurodevelopmental outcome in preterm infants. A new reliable proxy for brain volume is cranial volume, which can be measured routinely by 3-D laser scanning. The aim of this study was to develop reference charts for normal cranial volume in newborn infants at different gestational ages starting from late preterm for both sexes. Methods: Cross-sectional cohort study in a German university hospital, including singleton, clinically stable, neonates born after 34 weeks of gestation. Cranial volume was measured in the first week of life by a validated 3-D laser scanner. Cranial volume data was modelled to calculate percentile values by gestational age and birth weight and to develop cranial volume reference charts for girls and boys separately. Results: Of the 1698 included infants, 842 (50%) were female. Birth weights ranged from 1460 to 4830 grams (median 3370). Median cranial volume increased from 319 [interquartile range (IQR) 293-343] ml at 34 weeks to 469 [IQR 441-497] ml at 42 weeks and was higher boys then in girls. Conclusions: This study presents the first reference charts of cranial volume which can be used in clinical practice to monitor brain growth between 34-42 weeks gestation in infants.